Perbandingan Induksi Menggunakan Misoprostol dan Oxytosin - Grace Novaline Tampanatu; Nurul Qalbi (Al-Hayat: Natural Sciences, Health & Environment Journal, 2025)
Labor induction is the process of starting labor artificially from 24 weeks of gestation. Many studies have been conducted to determine the effectiveness of misoprostol and oxytocin, even comparing the use of the two for labor induction. Based on these studies, there appear to be different effects of misoprostol and oxytocin. The aim of this literature review is to determine maternal and fetal outcomes after induction of labor with misoprostol and oxytocin.The method used is through literature review searches from electronic databases, namely Google Scholar, Biomed Research International, Sage Open Medicine. Research published between 2017 and 2023. Of the five articles used in this literature review, three of them prefer misoprostol as an alternative for labor induction. Misoprostol is a safe alternative to labor induction.